THE HISTORICAL EVOLUTION OF THE PATRIARCHATE IN THE CHURCH OF THE EAST OVER ITS FIRST FOUR NATIONAL SYNODS - Roselin (Asian Horizons, 2014)
The patriarchate, as an institution, has existed in the Church from the earliest times and was recognized by the first ecumenical councils (OE 7). However this list of Eastern Patriarchates provided in the Canons of first Ecumenical councils did not mention the name of the Patriarchate of Seleucia-Ctesiphon which is so ancient and apostolic in its Christian origin. This study presents the evolution of the Patriarchate in this forgotten tradition as an indigenous autonomous development. Since Syro-Malabar Church is of this liturgical tradition, this study is relevant in its context too. Being one of the most vibrant Church among the Orientals we have to think about the true spirit behind the mind of the Church expressed in OE, 12: “Seeing that the patriarchal office in the Eastern Church is a traditional form of government, the Sacred Ecumenical Council ardently desires that new patriarchates should be erected where there is need, to be established either by an ecumenical council or by the Roman Pontiff.”